Lithuanian Economics: “Where are we From? Who are we? Where are we Going?” - Čekanavičius, Linas (Ekonomika, 2002)
The paper attempts to discuss and evaluate the potential of Lithuanian economic thought in the light of an increasing competition in the opening global “intellectual market”. Past and present of Lithuanian economic profession, as well as factors that influenced path of its development and determine the present status are extensively analyzed here. The conclusion is that despite many positive developments Lithuanian economics at large is still at the stage that deserves “infant industry” status, and that urgent motivators are imperative to promote its advance to the internationally acceptable academic level. One has to recognize the fact - however painful - that so far Lithuania was a kind of European province as far as the mainstream of the world economics development was concerned. Studies of economics in Lithuania had to be started virtually from scratch in 1920’s. Twenty years later the influx of modern economic ideas to Lithuanian academics and practice was brutally stopped by the events of WW2 and the subsequent Soviet occupation. During the whole Soviet period development of the Lithuanian economic thought was severely constrained by the enforced “straightjacket” of Marxism-Leninism. The crumbling down of the Soviet system and regained independence brought welcomed freedom to the economic thought, however this was not followed by the immediate jump in the quality of economic research. Twelwe years later East-West asymmetries in economic profession are still clearly visible. The main reasons for that are: inadequate remuneration of scholars that forces academic economists to look out for an additional job as source of supplementary income, and effectively discourages promising potential researchers from joining academics; lack of quantitative analysis skills by majority and English language skills by the considerable number of Lithuanian economists; poor library facilities and research infrastructure. The progress and future of Lithuanian science in economics heavily depend on the following factors: prevention of the “brain drain” from the local academic institutions to the private and government sector (internal ‘brain drain’) and abroad (external ‘brain drain’); stimulation of “brain influx” via provision of incentives for a young promising graduates to stay in academics; adoption of special “infant industry” status for the economics profession in Lithuania.